2019
DOI: 10.1038/s41408-019-0187-7
|View full text |Cite
|
Sign up to set email alerts
|

The role of cement augmentation with percutaneous vertebroplasty and balloon kyphoplasty for the treatment of vertebral compression fractures in multiple myeloma: a consensus statement from the International Myeloma Working Group (IMWG)

Abstract: Multiple myeloma (MM) represents approximately 15% of haematological malignancies and most of the patients present with bone involvement. Focal or diffuse spinal osteolysis may result in significant morbidity by causing painful progressive vertebral compression fractures (VCFs) and deformities. Advances in the systemic treatment of myeloma have achieved high response rates and prolonged the survival significantly. Early diagnosis and management of skeletal events contribute to improving the prognosis and quali… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
90
0
5

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 61 publications
(98 citation statements)
references
References 81 publications
3
90
0
5
Order By: Relevance
“…Severe anemia and renal failure may necessitate hospitalization and immediate initiation of antimyeloma treatment along with supportive care [22]. Spinal cord compression may necessitate immediate initiation of radiotherapy and/or orthopedic decompensation [40,41]. Orthopedic treatment of impeding fractures and radiotherapy for palliation of pain unresponsive to analgesics should not be postponed [40].…”
Section: General Recommendationsmentioning
confidence: 99%
“…Severe anemia and renal failure may necessitate hospitalization and immediate initiation of antimyeloma treatment along with supportive care [22]. Spinal cord compression may necessitate immediate initiation of radiotherapy and/or orthopedic decompensation [40,41]. Orthopedic treatment of impeding fractures and radiotherapy for palliation of pain unresponsive to analgesics should not be postponed [40].…”
Section: General Recommendationsmentioning
confidence: 99%
“…A retrospective analysis, with 18 myeloma patients who underwent vertebroplasty prior to autologous stem cell transplant showed that vertebroplasty could be done without affecting peripheral blood stem cell collection and transplant [109]. The current recommendation in myeloma associated vertebral collapse is to consider vertebral augmentation if it causes moderate or severe pain, and particularly if it affects mobilization [110] This is supported by a recently published national guideline based on the GRADE-approach [111] recommending vertebral augmentation as treatment in patients with painful vertebral lesions and malignant hematologic disease [112].…”
Section: Vertebral Augmentationmentioning
confidence: 99%
“…In theory, SSF + VP will provide a more effective fixation than PKP and therefore will also lead to better pain relief, but this is not the case. The reason may be because PKP provides sufficient stability to the vertebra and destroys the surrounding pain sensory nerves [19, 20].…”
Section: Discussionmentioning
confidence: 99%